Perinatal outcome in pregnancy complicated with oligohydramnios at term - Kumar, Abhijeet; Rao, P. S.; Kumar, Sanjeev; Mitra, Binay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Oligohydramnios is defined as AFI of less or equal to five cm. Various methods like NST, acoustic stimulation, and fetal Doppler velocimetry are helpful in assessment of fetal wellbeing and identifying those pregnancies at risk of adverse perinatal outcome. This study was undertaken to know the adverse perinatal outcome in pregnant women with oligohydramnios at term and to evaluate the value of AFI in predicting the subsequent fetal dis-tress and caesarean delivery. Methods: Analysis of pregnancy outcome in 50 cases with diagnosis of oligohydramnios by USG after 37 completed weeks of gestation compared with 50 controls with no oligohydramnios and matched for other variables. There were some inclusion and exclusion criteria used. The results were statistically analysed using parameters like mean, standard deviation and chi square test sensitivity, specificity, PPV, NPV were used. Results: There was significant difference between two groups in occurrence of non-reactive and re-active NST pattern. There is increased incidence of labour induction in women with AFI ≤5cm as compared with women with AFI >5cm. Increased occurrence of LBW (≤2.5kg) in women with oligohydraminos and increased LSCS rates in pregnancy complicated by oligohydramnios were observed. Conclusions: An AFI of ≤ 5cm detected after 37 weeks of gestation is an indicator of adverse perinatal outcome. AFI can be used as an adjunct to other fetal surveillance methods. AFI is a valuable screening test for predicting fetal distress in labour requiring caesarean section.